PEMBERDAYAAN KELOMPOK TANI DALAM PEMBUATAN PHOTOSYNTHETIC BACTERIA (PsB) DAN BIOSLURRY UNTUK MENDUKUNG PERTANIAN BERKELANJUTAN DI DESA MEDOWO KABUPATEN KEDIRI - Suprianto, Agung; Sumarmi, Sumarmi; Ririh Windayu, Cinde; Arinta, Dicky (LPPM Universitas Bina Bangsa, 2024)
Medowo Village in Kediri Regency has great potential in the agriculture and livestock sector, but still relies on expensive and hard-to-obtain chemical fertilizers. Additionally, the suboptimal management of livestock waste causes environmental pollution. This service program aims to empower farmers in Medowo Village through training in the production of organic fertilizer using Photosynthetic Bacteria (PsB) and bioslurry. The service methods include socialization, training, and mentoring the